Embedded grace : Christ, history, and the reign of God in Schleiermacher's dogmatics - Vander Schel, Kevin (2013)
"Scholars are now at work not only rethinking Schleiermachers relation to the modern and contemporary theological tradition, but re-examining the dogmatic intricacies and commitments within his texts. Situated within this revisionist milieu, the author takes up the important issue of the coordination of grace and history in Schleiermacher, arguing for its significance in understanding the dynamics of Schleiermachers dogmatics and its grounding and realization in Christology. The project not only continues the recasting of Schleiermachers work in its wider context, but unpacks the dogmatic network within the paramount texts, as well as bringing crucial texts to the fore often neglected in English language scholarship. As such, this volume performs an innovative rethinking of revelation, grace, history, Christology, and ecclesiology in Schleiermacher, with particular attention to the pivotal dogmatic volume, The Christian Faith, and the unpublished Ethics. A commanding volume for scholars and students in modern and contemporary theology" -- Publisher description.
Diverging theological paths -- Rationalizing the supernatural -- Charting an alternative -- Schleiermacher's critical theology -- The distinctive shape of Christian thought -- Schleiermacher's Christian faith -- The contingency of grace -- The distinctive shape of Christian action -- Schleiermacher's lectures on Christian ethics -- Divine grace and the historical unfolding of Christian action -- Conclusion: historically embedded grace.
Includes bibliographical references (pages 227-243) and index.
Keywords: Schleiermacher, Friedrich, -- 1768-1834.; Theology, Doctrinal -- History -- 19th century